Pengaruh Ultilitarian Value Terhadap Mobile App Loyalty Melalui Mobile App Engagement: (Studi Pada Pengguna Reddoorz Di Indonesia) - Yassin, Roandika Pratama; Dewi, Citra Kusuma (eProceedings of Management, 2024)
In this current era, traveling to various regions has been widely embraced by people, considering it as a part of theirlives. Coupled with numerous policies implemented by the government to enhance the tourism industry. In this digitalage, there have been significant changes in people's lifestyles, especially in meeting their needs. They desireconvenience in obtaining things simply by using their smartphones. Hence, various applications have emerged tofacilitate travelers in their journeys, one of which is the online hotel booking application. One of the online hotelbooking applications available is RedDoorz, which offers a variety of services that users need.The aim of this research is to understand the influence of Utilitarian Value on Mobile App Loyalty through MobileApp Engagement among RedDoorz application users in Indonesia. Data collection for this research was conductedby distributing questionnaires and using quantitative data analysis. The sample used in this study was 277respondents, analyzed using Smart-PLS version 3. Based on the research findings, it can be concluded that partially,the utilitarian value variable has a positive and significant effect on mobile app engagement. Partially, the mobileapp engagement variable has a positive and significant effect on mobile app loyalty. Furthermore, the utilitarian valuevariable has a positive effect on mobile app loyalty through mobile app engagement.Keyword-mobile app, booking online, hotel, RedDoorz